ANALISA EMISI GAS BUANG KENDERAAN RINGAN YANG DIUJI DI DINAS PERHUBUNGAN KOTA MEDAN - Junaidi Junaidi; Din Aswan Amran Ritonga; Maulana Siddiq Sitepu (Universitas Harapan Medan, 2019)
The use of biodiesel in boilers has great benefits because it can reduce exhaust emissions. The purpose of this study is to test the quality of diesel and biodiesel raw materials as fuel from boilers, analyze the concentration of polluting gases (NOx, CO2, SO2) from the combustion of biodiesel and diesel oil experimentally. The combustion system in boilers tends to be simpler than compression ignition as done in diesel engines. This research was conducted experimentally on a fire tube boiler, with a heat input rate of 60,000 kCal / hour and a pressure of 3 bar using biodiesel made from CPO (crude palm oil) as fuel. The mixture varies on 0, 5, 10, 15, 20 and 25% biodiesel in a mixture with biodiesel (B0, B5, B10, B15, B20 and B25). This research was conducted experimentally by testing exhaust gas emissions produced from exhaust gas chimneys which are expected to produce low exhaust emissions and are environmentally friendly. The results showed that the use of biodiesel reduces gas emissions by increasing the value of biodiesel in the mixture. The results showed that the lowest exhaust gas emission was around 4.142% (NOx); 12.50% (SO2) and 7.9% (CO2) are contained in a mixture of 25% biodiesel in fuel (B25).